The epic of Bidasari (and other tales, including) Sedjarat Melayou, The princess Djouher-Manikam, Makota Radja-Radja - Starkweather, C. C.; Devic, M.; Marre, Aristide 1823-1918 (Silverfish Malaysian classics, 2012)
"Easily the most charming poem of Malayan Literature is the Epic of Bidasari. it has all the absorbing fascination of a fairy tale. We are led into the dreamy atmosphere of haunted palace and beauteous plaisance; we glide in the picturesque imaginings of the oriental poet of the charm of all that is languorously seductive in nature into the shadowy realms of the supernatural. At one moment, the sturdy bowman or lithe and agile lancer is before us in a hurrying column, and at another we are told of the mystic sentinels from another world, of djinns and demons and spirit-princes. All seems shadowy, vague, mysterious, entrancing. We hope that no philosopher, philologist, or ethnologist will persist in demonstrating the sun-myth or any other allegory from this beautiful poem. It is a story, a charming tale to while away an idle hour, and nothing more. All lovers of the simple, the beautiful, the picturesque should say to such learned peepers and botanizers, Hands off! let no learned theories rule here. Leave this beautiful tale for artists and lovers of the story pure and simple. Seek no more moral here than you would in a rose or lily or a graceful palm. Light, love, colour, sympathy, engaging fascination - these may be found alike by philosopher and winsome youth. The story is no more immoral than a drop of dew or a lotus bloom and, as to interest, in the land of the improviser and the story-teller one is obliged to be interesting. For there, the audience is either spellbound, or quickly fades away and leaves the poet to realize that he must attempt better things.